Intervención farmacéutica domiciliaria a pacientes con tratamiento antihipertensivo - Sigüenza Aguilar, Cecilia Beatriz (2011)
ABSTRACT The aim of the present study was to set up the impact of a pharmaceutical intervention in 39 patients diagnosed with essential hypertension that went to the Pharmacy called “Pharmacy Health and Life” in Cajamarca city, held in the period from October 2009 to December 2010. A quasi-experimental design was used, through a home pharmacotherapy monitoring to patients who qualify with the inclusion criteria, determining parameters such as blood pressure, body mass index, degree of satisfaction to pharmacist, the degree of adherence to their antihypertensive treatment, as well as the level of knowledge about hypertension. Determinations with pharmaceutical intervention (pre-post test) were done, as well as without pharmaceutical information. The results show a positive impact in the pharmaceutical intervention done in the hypertensive patients, after ten months of the study was done.